Synthesis of ZnO/CNT Nanocomposites for Ultraviolet Sensors - Basit, Maryam; Abbas, Murrawat; Ahmad, Naeem; Javed, Sofia; Shah, Nazar Abbas (Frontiers in Materials, 2022)
Zinc oxide/Carbon nanotubes (ZnO/CNTs) nanocomposites are developed on gold (Au) coated un-polished Si p-type (100) substrates with 2, 4, 6, 8 and 10 nm thicknesses by VLS method. One set of Au coated Si substrates are annealed to develop Si-Au samples for better nucleation. XRD, FE-SEM, Raman and PL spectroscopic characterizations are used to study structural, morphological and optical properties on annealed and un-annealed catalyst layer with various Au thicknesses samples. In XRD results, the ZnO/CNTs nanocomposites are observed with higher crystallinity and purity of phase. FE-SEM images showed variety of nanostructures with variation in morphologies with respect to Au thickness in annealed and un-annealed samples. Clear indication of high defects concentration and high crystallinity is observed in Raman spectra. It is observed in PL spectral that preferred peak orientation with shift 4 nm in un-annealed Au layer and 9 nm in annealed Au layer samples, which exhibited formation of ZnO/CNTs nanocomposites. Efficient sensing is observed in 6 nm thickness Au layer in un-annealed sample. Annealed Au coated Si samples at 8 nm and 10 nm thicknesses showed efficient UV sensing with quick response and recovery time.